The Coupled Effect of Temperature and Carbonation on the Corrosion of Rebars in the Simulated Concrete Pore Solutions - Jiezhen Hu; Xuequn Cheng; Xiaogang Li; Peichang Deng; Gui Wang (Journal of Chemistry)
The reinforced concrete structures have to survive high temperature and carbonation at low latitude region. The research on the effect of temperature and the effect of carbonation are vital to the corrosion of the rebars in concrete structures. The coupled effect of temperature and carbonation on the corrosion of rebars was researched by using the open circuit potential (OCP), the electrochemical impedance spectroscopy (EIS), and the potentiodynamic polarization (PP) measurement in the simulated concrete pore solutions (SPSs). The high temperature environment is conducive to the formation of passivated surface of rebars in SPSs, but the dissolution velocity of passivated surface is higher. The rebars have the greater capacity of passivity at lower temperature. The corrosion rate of rebars at higher temperature is smaller in moderate pH value (10.6) SPSs. The rebars suffer from serious corrosion in the pH = 9.6 SPSs at 318 K temperature.